2023
DOI: 10.1001/jamanetworkopen.2023.18715
|View full text |Cite
|
Sign up to set email alerts
|

Association of Open Reduction and Internal Fixation With Volar Locking Plate for Distal Radius Fractures With Patient-Reported Outcomes in Older Adults

Abstract: ImportanceRandomized clinical trials (RCTs) and meta-analyses have reported inconsistent conclusions regarding optimal distal radius fracture (DRF) treatment in older adults and are limited due to the inclusion of cohort studies with small sample sizes. A network meta-analysis (NMA) addresses these limitations by only synthesizing direct and indirect evidence from RCTs and may clarify optimal DRF treatment in older adults.ObjectiveTo examine DRF treatment results in optimal short-term and intermediate-term pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…A recent network meta-analysis compared short-term (up to 3 months) and intermediate-term (3 to 12 months) of DASH and PRWE scores following different treatment approaches of distal radial fractures and reported that internal fixation with volar lock plating made no increase in 1-year complication rates compared to other treatment options. They proposed shared decision-making with patients to identify patient preferences regarding recovery to determine optimal treatment [24].…”
Section: Resultsmentioning
confidence: 99%
“…A recent network meta-analysis compared short-term (up to 3 months) and intermediate-term (3 to 12 months) of DASH and PRWE scores following different treatment approaches of distal radial fractures and reported that internal fixation with volar lock plating made no increase in 1-year complication rates compared to other treatment options. They proposed shared decision-making with patients to identify patient preferences regarding recovery to determine optimal treatment [24].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies on postoperative QoL found that increases in PCS and MCS scores mostly occur within the first six months postoperatively [ 50 , 51 ]. Based on stable reduction, both internal and external fixation could result in satisfactory fracture recovery in the short term postoperatively [ 4 8 ]. However, the time it takes for patients to return to their previous functional status in society varies.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment methods for fractures have notably progressed with continuous advancements in medical technology. Internal and external fixations are the two commonly used surgical approaches for stabilizing the fracture site and promoting healing and recovery [ 4 8 ]. However, besides the physical recovery process, the psychological well-being of fracture patients is the other important dimension that should be carefully considered.…”
Section: Introductionmentioning
confidence: 99%
“…To address these issues, authors from Ann Arbor (Michigan, USA) conducted a network meta-analysis (NMA) using data from RCTs conducted between 2000 and 2022 in older adults aged 50 years and over. 1 The advantage of a NMA is that it allows for indirect comparison, so by using a range of studies comparing A versus B, and A versus C, the benefit of B versus C can also be calculated. The study assesses patient-reported outcome measures (PROMs) like Disabilities of the Arm, Shoulder and Hand questionnaire (DASH) and Patient-Rated Wrist Evaluation (PRWE) scores.…”
Section: Volar Locking Plate For Distal Radius Fractures With Patient...mentioning
confidence: 99%